2011
DOI: 10.1088/1742-6596/304/1/012057
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of titanium dioxide nanoparticles toxicity and uptake by plants

Abstract: Abstract. Nanoparticles (NP) are introduced in a growing number of commercial products and their production may lead to their release in the environment. Plants may be a potential entry point for NP in the food chain. Up to now, results describing NP phytotoxical effects and plant accumulation are scarce and contradictory. To increase knowledge on titanium dioxide NP (TiO 2 -NPs) accumulation and impact on plants, we designed a study on three plant species, namely wheat (Triticum aestivum), oilseed rape (Brass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 14 publications
(14 reference statements)
2
27
1
1
Order By: Relevance
“…2). The isoelectric point (pH iep ) of TiO 2 NPs in UHPW corresponds to pH 7.12, which is in good agreement with those pH iep reported in other studies with pH values varying from 6.7 to 7.5 (Fernández-Nieves et al, 1998;Finnegan et al, 2007;Larue et al, 2011). The hydrodynamic diameter of the NPs has increased drastically with increasing pH to about 7.0 (Fig.…”
Section: Properties Of the Freshly Suspended Tio 2 Nps In Ultra-pure supporting
confidence: 90%
“…2). The isoelectric point (pH iep ) of TiO 2 NPs in UHPW corresponds to pH 7.12, which is in good agreement with those pH iep reported in other studies with pH values varying from 6.7 to 7.5 (Fernández-Nieves et al, 1998;Finnegan et al, 2007;Larue et al, 2011). The hydrodynamic diameter of the NPs has increased drastically with increasing pH to about 7.0 (Fig.…”
Section: Properties Of the Freshly Suspended Tio 2 Nps In Ultra-pure supporting
confidence: 90%
“…In the cytoplasm, nanoparticles approach to different cytoplasmic organelles and interfere with different metabolic processes of the cell (Moore 2006). Furthermore, Larue et al (2011) studied the uptake of TiO 2 nanoparticles in wheat and observed the nanoparticles in parenchyma and vascular tissues of the root. Lin and Xing (2008) examined the cell internalization and upward translocation of ZnO nanoparticles in Lolium perenne (ryegrass).…”
Section: Uptake Translocation and Fate Of Nano-fertilizers In Plantsmentioning
confidence: 99%
“…Ion PIXE provides multi-elemental capability, which allows the simultaneous comparison of distribution of several elements inside the same specimen [401][402][403][404][405][406][407][408][409][410].…”
Section: Ion Beam Analysis Techniquesmentioning
confidence: 99%